Lancastrian rule and the resources of the prince of Wales, 1456–61. Issue 3 (26th May 2016) - Thornton, Tim
ABSTRACT: This paper challenges the idea that the Lancastrian regime of the late 1450s was distinctive for its reliance, from the midlands, on the principality of Wales and the palatinate of Chester. The common emphasis on its association with Cheshire is a product of the late sixteenth century, and, beyond that, contemporary and near-contemporary perceptions even of a link with the midlands were limited. When the court moved to the midlands in 1456 the resources of the principality and earldom were far from easily accessible, and even thereafter the efforts made to draw on them were limited in their ambition and impact. Financial flows to the regime were restricted, and the political networks established, especially in the North and in Cheshire, were limited and highly dependent on the Stanleys. By 1459–60, therefore, the regime found little to rely on there, and the Yorkists were able to supplant them with relative ease.